'Total environ–mentality' culture: re–engineering the American nuclear power industry through learning from multi–national, multi–level experience. (4th August 2014) - Carayannis, EIias
Applying lessons learned at the national, the utility, and the plant level, from selected segments of the world–wide nuclear power industry, might facilitate an environmentally acceptable renaissance in the US. It can be deduced that the core of all the continuous quality improvement and re–engineering programmes, championed by the top management of nuclear power utilities around the world, consists of two missions: (i) to insulate society from foreseeable and unacceptably high environmental risks, and (ii) to improve continuously the design and management of nuclear technology (including nuclear waste management and environmental risk management systems) by (a) learning actively, and both explicitly and tacitly, through feedback from individual and organisation experience, and (b) learning how to learn and how to learn–how–to–learn better and faster, and both explicitly and tacitly, through feedback from acquired and shared individual and group/organisational experience.